2016
DOI: 10.1080/08916934.2016.1199020
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo expanded regulatory T cells CD4+CD25+FoxP3+CD127Low develop strong immunosuppressive activity in patients with remitting-relapsing multiple sclerosis

Abstract: Multiple sclerosis (MS) is an autoimmune disease characterized by defect in regulatory function of CD4CD25 T cells. We demonstrated difference in proportion of regulatory T cells CD4CD25FoxP3CD127 (Tregs) within the same patients' relapse and remission. Proportion of peripheral Tregs (pTregs) dropped almost two times in the relapse compare to remission. Levels of pTregs in patients' remission were lower than in healthy donors. Suppressive ability of pTregs was decreased in MS patients compared to healthy donor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 52 publications
1
15
0
Order By: Relevance
“…Interestingly, following expansion the immunophenotype and suppressive activity of Tregs from advanced Alzheimer’s disease patients were comparable to those of HC. A similar pattern has been observed following ex vivo expansion of dysfunctional Tregs in other neurological disorders including multiple sclerosis ( Lifshitz et al , 2016 ) and ALS ( Alsuliman et al , 2016 ; Thonhoff et al , 2018 ).…”
Section: Discussionsupporting
confidence: 74%
“…Interestingly, following expansion the immunophenotype and suppressive activity of Tregs from advanced Alzheimer’s disease patients were comparable to those of HC. A similar pattern has been observed following ex vivo expansion of dysfunctional Tregs in other neurological disorders including multiple sclerosis ( Lifshitz et al , 2016 ) and ALS ( Alsuliman et al , 2016 ; Thonhoff et al , 2018 ).…”
Section: Discussionsupporting
confidence: 74%
“…Many early studies in MS assumed CD4 + CD25 + Treg were a homogenous population of naïve Foxp3 + Treg. In 29 studies we identified that examined CD4 + CD25 + Treg either without or with Foxp3/low CD127 expression in MS compared to healthy donors; 12 studies found no difference in MS compared to HD in frequency 5 , 6 , 9 , 24 , 25 , 27 30 , 32 , 34 , 37 while nine found reduced Treg 7 , 10 , 11 , 14 – 17 , 19 , 20 , and three found reduced Treg during relapses 8 , 12 , 19 . Other studies reported reduced Treg in stable MS but an increase in Treg associated with relapses 7 and progressive MS 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Human Treg are best defined as CD4 + CD25 + CD127 lo Foxp3 + but use of Treg makers is not consistent. In 29 studies we identified of CD4 + CD25 + Treg in blood of MS patients 5 12 , 14 – 17 , 19 , 20 , 22 25 , 27 37 , only 20 stained for Foxp3 6 8 , 10 12 , 14 , 15 , 17 , 19 , 22 24 , 28 32 , 34 , 36 and 14 for CD127 6 , 11 , 14 , 16 , 19 , 20 , 23 , 30 , 31 , 33 37 . CD4 + CD25 + CD127 lo Foxp3 + T cells are a heterogeneous population that can include Treg but also includes activated effector cells that are transiently induced to express CD25 and Foxp3 but this Foxp3 expression is unstable 38 41 .…”
Section: Introductionmentioning
confidence: 99%
“…The sensitization did not alter CD4 1 T-cell composition significantly in all lymph tissues examined (Fig 7, A-C) but diminished FoxP3 1 CD4 1 T-cell counts substantially when compared with those in nonsensitized mice, regardless of which subsets of the cells were analyzed in all 3 lymph tissues, with the exception of mLNs, in which total FoxP3 1 CD4 1 T-cell counts were unaltered (Fig 7, D-F). These CD25 1 FoxP3 1 CD127 2 CD4 1 T cells are commonly referred to as Treg CD4 1 T cells, [37][38][39][40][41] although their inhibitory function needs to be verified in the future. In general, all 3 EPITs increased the level of effector/memory CD4 1 T cells concurrent with a reciprocal decrease in numbers of naive CD4 1 T cells in the spleens and mLNs when compared with those in sham-treated mice (Fig 7, B and C).…”
Section: Pld-mna Induces Immune Tolerance and Attenuates Allergic Resmentioning
confidence: 99%